Structural, Dielectric, Optical and Magnetic Properties of Ti3+, Cr3+, and Fe3+: PVDF Polymer Films. (24th September 2013) - Reddy, M. Obula; Reddy, L. Raja Mohan
Abstract : Highly transparent and very clear nature of PVDF: Ti 3+, PVDF: Cr 3+, and PVDF: Fe 3+ polymer films of good quality have been synthesized by employing solution casting method. XRD profiles have confirmed semicrystalline structures in α -, β -, and γ -PVDF phases. IR spectra have confirmed these findings and revealed some structural defects such as monofluorinated alkenes. Emission spectra reveal that PVDF: Ti 3+ has a blue emission, PVDF: Cr 3+ has blue emission, and PVDF: Fe 3+ red emission was observed. The conductivity and dielectric measurements have also been carried out as function of frequency and temperature changes. Due to the presence of the transition metal ions in these films, significant improvement in the ionic conductivity has been noticed. The dielectric behaviors of these films have been analyzed using dielectric permittivity (ε 1 ), dissipation factor (tan δ ), and impedance spectra ( Z 1 and Z 11 ). VSM measurements have confirmed that the PVDF: Ti 3+ exhibits antiferromagnetic nature, PVDF: Cr 3+ film ferromagnetic nature, and PVDF: Fe 3+ film strong paramagnetic nature. Thus, the present study has successfully explored the fact that these optical materials are also potential enough in both conductivity and magnetic properties for their use in applications suitably.